1988
DOI: 10.1007/bf00395552
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart disease and urinary albumin excretion rate in Type 2 (non-insulin-dependent) diabetic patients

Abstract: Associations between overnight urinary albumin excretion rate and prevalent coronary heart disease and its major risk factors were examined in a cross-sectional study of 141 Type 2 (non-insulin-dependent) diabetic patients. Mean albumin excretion rate was higher in men (geometric mean 13.5 micrograms/min; 95% confidence interval 10.3-17.6) than women (7.5 micrograms/min; 5.7-9.8, p less than 0.01). In diabetic men and women mean albumin excretion rate was higher in those with electrocardiographic and/or sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
82
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(95 citation statements)
references
References 17 publications
13
82
0
Order By: Relevance
“…Other classic cardiovascular risk factors were also associated with coronary heart disease in this study, and these include micro-or macroalbuminuria or both, which are well established as independent cardiovascular risk factors in NIDDM [36]. Plasma total cholesterol and apoB levels were also significantly associated with coronary heart disease in our patients, despite the more frequent use of hypolipidaemic treatment in the CHD + group.…”
Section: Discussionsupporting
confidence: 52%
“…Other classic cardiovascular risk factors were also associated with coronary heart disease in this study, and these include micro-or macroalbuminuria or both, which are well established as independent cardiovascular risk factors in NIDDM [36]. Plasma total cholesterol and apoB levels were also significantly associated with coronary heart disease in our patients, despite the more frequent use of hypolipidaemic treatment in the CHD + group.…”
Section: Discussionsupporting
confidence: 52%
“…Hypertension is a risk factor of cardiovascular events in Type 2 diabetic patients with microalbuminuria [38]. It seems established that high blood pressure in these patients should be adequately controlled, regardless its pathophysiological mechanism(s) behind the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Moreover, in people with NIDDM, it is associated with other risk factors for CVD such as hypertension, 3±7 hyperglycaemia, 3±7 obesity, 3,6 and dyslipidaemia. 3 Studies of elderly non-diabetic subjects in the general population have also shown a positive relationship between degree of albuminuria and increased CVD morbidity, 7 early mortality, 7,8 and risk factors for CVD. 9±16 These observations led Yudkin,7 Cruickshank 17 and Haffner 9 to propose that microalbuminuria might represent a marker of CVD risk in nondiabetic subjects.…”
Section: Introductionmentioning
confidence: 99%